Kawasaki Disease Shock Syndrome: Think Earlier, Treat Intensively - Özlem Sarıtaş Nakip; Selman Kesici; Ayşe Ünal Yüksekgönül; Yelda Bilginer; Seza Özen; Benan Bayrakcı (Galenos Yayinevi, 2023)
Kawasaki disease shock syndrome (KDSS) is a rare disease characterized by cardiovascular collapse that requires aggressive supportive and immunomodulatory therapy. The purpose of this report is to highlight our management strategies in KSSS patients. Patients who were followed up with a diagnosis of Kawasaki disease in intensive care unit and those who met the criteria for Kawasaki disease shock syndrome were included in the study. Data were obtained retrospectively from hospital records. Between 2005 and 2020, 5 patients with Kawasaki disease were followed up in the pediatric intensive care unit. Three children in the adolescent age group were diagnosed with Kawasaki disease shock syndrome. Two patients had severe coronary artery dilatation, one patient required therapeutic plasma exchange due to multiple organ failure. Kawasaki disease shock syndrome is a serious, life-threatening form of Kawasaki disease and should be suspected in children with severe inflammation and significant cardiac involvement. Administration of plasmapheresis in addition to steroid therapy appears to be effective in controlling severe disease and should not be delayed.